2017
DOI: 10.1177/1363460717699771
|View full text |Cite
|
Sign up to set email alerts
|

“Different than an infantry unit down in Georgia”: Narratives of queer liberation in the post-DADT military

Abstract: More than five years out from its implementation, we still know relatively little about how members of the US military and its ancillary institutions are responding to the repeal of Don't Ask, Don't Tell. Contrary to what one might expect given the long history of LGBTQ antipathy in the military, I found in interviews with Boston area Reserve Officer Training Core (ROTC) cadets unanimous approval for the repeal of DADT. When pressed to explain why there was so much homogeneity of favorable opinion regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Future research should look to replicate the findings reported here with service members at multiple levels of the organization. Further, some research suggests, for example, a faulty urban versus rural binary narrative regarding attitudes toward LGB people [46]. How do the findings here regarding transgender people contribute to this literature and our understanding of transgender experiences?…”
Section: Discussionmentioning
confidence: 99%
“…Future research should look to replicate the findings reported here with service members at multiple levels of the organization. Further, some research suggests, for example, a faulty urban versus rural binary narrative regarding attitudes toward LGB people [46]. How do the findings here regarding transgender people contribute to this literature and our understanding of transgender experiences?…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates an enthusiasm, at least among those who were previously expelled, to participate in military service. Meanwhile, analyses of military attitudes toward transgender people show movement toward acceptance, especially among soon‐to‐be officers in ROTC programs (Connell, ; Ender, Rohall, & Matthews, ). If the transition into trans inclusion is as smooth as the DADT repeal seems to have been and as advocates argue it will be (Pollock & Minter, ), it could go a long way toward further bolstering that acceptance.…”
Section: The Impact Of Open Service In the Us Militarymentioning
confidence: 99%